2021
DOI: 10.1021/acsami.0c18119
|View full text |Cite
|
Sign up to set email alerts
|

SEI Formation on Sodium Metal Electrodes in Superconcentrated Ionic Liquid Electrolytes and the Effect of Additive Water

Abstract: We have previously reported that water addition (∼1000 ppm) to an N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide (C 3 mpyrFSI) superconcentrated ionic liquid electrolyte (50 mol % NaFSI) promoted the formation of a favorable solid electrolyte interphase (SEI) and resulted in enhanced cycling stability. This study reports the characterization of Na−metal anode surfaces cycled with these electrolytes containing different water concentrations (up to 5000 ppm). Morphological and spectroscopic characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 64 publications
1
48
0
Order By: Relevance
“…On all spectra, this FSI signal contains one extremely sharp and one broader component (Figure S7) that can be attributed to mobile, liquid-like nondegraded FSI − anions and non-or less mobile confined FSI containing species, such as LiFSI. Ferdousi et al 61 recently reported the formation of complexes suggested to be Na 2 [SO 3 -N-SO 2 F]•nH 2 O (n = 0− 2) in the Na system, resulting from the partial decomposition of FSI. In these complexes, the local environment of fluorine is expected to be close to that in FSI anion and the corresponding 19 F NMR shift close to that of the nondegraded FSI signal.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…On all spectra, this FSI signal contains one extremely sharp and one broader component (Figure S7) that can be attributed to mobile, liquid-like nondegraded FSI − anions and non-or less mobile confined FSI containing species, such as LiFSI. Ferdousi et al 61 recently reported the formation of complexes suggested to be Na 2 [SO 3 -N-SO 2 F]•nH 2 O (n = 0− 2) in the Na system, resulting from the partial decomposition of FSI. In these complexes, the local environment of fluorine is expected to be close to that in FSI anion and the corresponding 19 F NMR shift close to that of the nondegraded FSI signal.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…2−4 Recently, high salt concentration (or superconcentrated) organic solvents and their nonflammable alternatives, such as ionic liquid (IL) electrolytes, were found to be successful in achieving high Coulombic efficiency for metal deposition with a uniform morphology, likely resulting from the formation of a favorable solid−electrolyte interphase (SEI). 5−8 Other attempts have been made to enhance the transport properties and electrochemical behavior of superconcentrated electrolytes in the applicable temperature range by introducing additional low molecular weight components, such as water 9 and/or organic solvents. 10−12 Moreover, the optimal cycling protocols have been also designed to deliver long-term stable cycling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Unfortunately, the Na metal anode still faces severe problems in its practical applications. , During the cycling process, uneven Na plating/stripping, unstable solid electrolyte interphase (SEI), and large volume expansion can induce Na dendrite growth and active Na loss, eventually leading to low Coulombic efficiency (CE), short cycling life, and safety hazards. , To address the abovementioned issues, various strategies have been employed, mainly including the optimization of liquid electrolytes, , the introduction of artificial SEI films on the Na metal surface, , the use of solid-state electrolytes, and the construction of three-dimensional (3D) conductive hosts. Among them, three-dimensional (3D) hosts have the merits of good conductivity and large surface area, which can not only significantly reduce the local current density but also alleviate the Na volume change during cycling. Thus, Na dendrite growth can be effectively suppressed and the CE of the Na metal anode can be largely improved .…”
Section: Introductionmentioning
confidence: 99%